Thermal and Optical Properties of Porous Nanomesh Structures for Sensitive Terahertz Bolometric Detection - Ryoko Yamamoto; Akira Kojima; Nobuyoshi Koshida; Isao Morohashi; Kazuhiko Hirakawa; Ya Zhang (Sensors, 2022)
Terahertz (THz) electromagnetic waves are attractive for use in nondestructive and biocompatible sensing applications. Thermal sensors are widely used for THz detection owing to the small photon energies of THz radiation, where this requires materials with low thermal conductivity and a small heat capacity to ensure the sensitive and fast operation of the sensors. In this study, we investigated the thermal and optical properties of porous nanomesh structures for sensitive THz bolometric detection. Nanometer (nm)-scale hole array structures were formed on gallium arsenide (GaAs) microelectromechanical system (MEMS) beams to improve their thermal properties. The thermal conductance of the porous MEMS beams was obtained by measuring their thermal bandwidths; it was found to decrease by as much as ~90% when the porosity (P) of the porous nanostructure was increased to ~0.69. We also measured the THz absorptance of the porous hole array structure. The results show that although the porous nanostructure has a much smaller area than the bulk material, it maintained a high coefficient of THz absorptance because the featured size was much smaller than the THz wavelength. The measured absorptance agreed well with that calculated by using the Drude model. These results demonstrate that the porous nanomesh structure is promising for developing highly sensitive THz thermal sensors.